Posttraumatic stress disorder symptoms among Chinese college students following the COVID-19 outbreak - Wang, Jie-Yu; Li, Qi; Liu, Wei; Yang, Yang; Wang, Xiao-Guang; Liu, Chun-Yan; Shu, Xi-Ji; Xue, Li; Shi, Yan-Wei (Frontiers in Neuroscience, 2023)
Objective This study examined the prevalence of posttraumatic stress disorder (PTSD) symptoms in college students 1 month after the lockdown of Wuhan to identify possible risk factors for PTSD symptoms in a cross-sectional study. Methods Out of 10,502 who responded, 9,274 students impacted by the COVID-19 pandemic were included in our study. PTSD symptoms was evaluated by the Impact of Event Scale-revised (IES-R). Anxiety/depression symptoms were evaluated by the Kessler Psychological Distress Scale (K10). Personality traits, coping style, and social support were assessed by the Eysenck Personality Questionnaire-Revised Short Scale for Chinese (EPQ-RSC), the Simplified Coping Style Questionnaire (SCSQ), and the Social Support Rating Scale (SSRS). Logistic regression analysis was utilized to further explore risk factors for PTSD symptoms. Results More than 1 month after the COVID-19 outbreak, 13.1% of college students developed PTSD symptoms, indicating that COVID-19 associated stressful experiences were connected with PTSD symptoms. After the COVID-19 outbreak, subjects with symptomatologic PTSD symptoms were more likely to experience strained relationships with their family, to have close contact with COVID-19 patients and to drop out of college. The logistic regression model demonstrated the association factors of PTSD symptoms. Neuroticism, psychoticism and an avoidant coping style were associated with increased risk for PTSD symptoms, while an active coping style was protective against PTSD symptoms during this pandemic. Conclusion The results showed that PTSD symptoms was prevalent in Chinese college students 1 month after the COVID-19 outbreak. Effective psychological support work should be carried out accordingly.